Importance of workplace wellness programmes in protection of employee health - Lazarević Snežana; Lukić-Nikolić Jelena (College of Sports and Health, Belgrade, 2021)
Every organization strives to have productive, creative, responsible employees, who constantly seek to acquire new knowledge and skills, who are motivated, loyal and engaged, and psycho-physically healthy. However, modern and dynamic business conditions, constantly growing demands and needs of consumers, setting new goals and tasks, increasing the level of responsibility and standards, and often setting expectations from employees too high are just some of the many pressures and sources of stress to which employees are permanently exposed in their workplace. Caring about employees, and safety and health protection at work is one of the important activities of the business function of human resource management. The priority task of experts in this field is to act preventively against stressors by creating various methods and techniques for their efficient and effective management. One of the techniques that is becoming increasingly popular in socially responsible organizations, are wellness programmes. By organizing and implementing these programmes, the management of the organization shows that it cares and acts preventively to maintain the safety and protection of the health of its employees, and the employees themselves acquire new knowledge and healthy life habits through these programmes. This paper points out the importance and role of wellness programmes, as important activities of strategic human resource management of modern organizations, which occupies a significant position in the protection and prevention of employee health. Also, the paper outlines all the important elements that management should keep in mind when designing and implementing wellness programmes in order for them to adequately influence the improvement of physical and mental health of employees.